Analisis Perilaku Konsumtif Masyarakat Dengan Perubahan Tarif Pajak, Kebutuhan Dasar Dan Pendapatan Keluarga - Suhartono, Edy; Mustofa, Moh; Ardyani, Ryzki Novica; Septiani, Elsi Dwi (JURNAL DIMENSI, 2025)
This study aims to analyze how the 11% VAT, basic commodity prices, and household income interact and shape the consumption behavior of residents. This study employs a descriptive approach and quantitative analysis with 96 household respondents in Bojonegoro City, analyzing the relationship between the 11% VAT, prices of basic necessities, and income on consumer behavior using a questionnaire assessed with a Likert scale. The study found that the 11% VAT and prices of primary commodities have a significant and positive influence on the consumption behavior of residents in Bojonegoro Regency, while income has no impact. However, in the F-test, the variables studied were found to contribute significantly to shaping the consumption behavior of the community. The findings of this study are intended to serve as a basis for the government, business community, and society in formulating adaptive strategies in response to changes in economic conditions.